Buying into inequality: a macroeconomic analysis linking accelerated obsolescence, interpersonal inequality, and potential for degrowth - Antoine Monserand (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
This article establishes a theoretical link between accelerated obsolescence and interpersonal inequality of income and wealth. The author designs a simple stock–flow consistent macroeconomic model and simulates an acceleration of obsolescence in different budget and fiscal policy scenarios. His results show that, despite the increase in revenues generated by extra constrained expenditures and the associated multiplicative effects, the economic consequences of fast obsolescence remain negative. As effective disposable income declines for workers and either decreases less or increases for capitalists, income and wealth inequalities are exacerbated. Hence an acceleration of obsolescence has detrimental effects both on distributive and on environmental grounds. Conversely, in line with the degrowth paradigm, the author shows how slowing down obsolescence may be sensible both socioeconomically and environmentally. It would be beneficial to wage earners while reducing pressures on the environment; the only losers would be profit earners.
Keywords: 330; obsolescence; inequality; ecological macroeconomics; degrowth; stock–flow consistent modellingE12; E21; E62; P46; Q52